A Statistical Explanation of the Dunning–Kruger Effect - Magnus, Jan R.; Peresetsky, Anatoly A. (Frontiers in Psychology, 2022)
An explanation of the Dunning-Kruger effect is provided which does not require any psychological explanation, because it is derived as a statistical artefact. This is achieved by specifying a simple statistical model which explicitly takes the (random) boundary constraints into account. This model fits the data almost perfectly.